Manually operated onions grading machine for the agricultural product / Intan Nur Mawaddah Mohd Sham - Mohd Sham, Intan Nur Mawaddah (2023)
Onion grades are determined by the various onion sizes. The method of isolating onion size nowadays is quite complicated as it requires a lot of manpower at the same time. This will take more time to isolate the onions. So, this project will help more parties by reducing segregation time and the large number of manpower. This project requires only a small amount of manpower and is carried out manually only. Method of using this machine is, the user has to insert the onion into the roller and turn the lever on the side of the machine. The onion will fall down according to the size available on the loop. At the end of the process, many onions can be separated into desired grade based on their size in a short time in large quantities. The target market for this project is small industry.